Climbing the corporate ladder and within-person changes in narcissism: Reciprocal relationships over two decades - WILLE, Bart (Institutional Knowledge at Singapore Management University, 2019)
Prior research demonstrated that narcissism fosters the attainment of higher managerial ranks in organizations. However, it is not known whether climbing the corporate ladder also fosters the development of narcissism over time. Whereas prior work consistently adopted a unidirectional perspective on narcissism and career attainment, this study presents and tests a bidirectional perspective, incorporating long-term development in narcissism in relation to and in response to long-term upward mobility. To this end, a cohort of highly educated professionals was assessed three times over a 22-year time frame. Extended latent difference score modeling showed that, over the entire interval, within-person changes in narcissism were positively related to within-person changes in upward mobility. This was in line with our first hypothesis which described a positive co-development between both processes over time. However, when reciprocity was analyzed in a time-sequential manner, i.e. from the first career stage to the second, we found more support for narcissism predicting later upward mobility (Hypothesis 2) than for the reverse effect from mobility to later change in narcissism (Hypothesis 3). Moreover, this effect from upward mobility to subsequent change in narcissism was negative, indicating that higher career attainment during the first career stage inhibited (rather than fostered) subsequent growth in narcissism. In sum, these results indicate that narcissism continues to demonstrate room for development over the course of people's careers. However, future research is needed to further clarify the exact nature of the effects that career experiences such as upward mobility have on this developmental process.